MENGEMBANGKAN SENI KARAWITAN MELALUI PENYELENGGARAAN FESTIVAL: DARI KAMPUS KE MASYARAKAT - Sartini, Sartini; Supartiningsih, Supartiningsih; Maharani, Septiana Dwiputri; Muthmainnah, Lailiy (Kumawula: Jurnal Pengabdian Kepada Masyarakat, 2026)
Traditional arts tend to lose popularity compared to pop culture. This also applies to Javanese gamelan art. Many gamelan instruments are in disrepair, and the public's desire to participate in preserving gamelan is declining. One reason is the lack of performance spaces, even though the potential of gamelan instruments, supporting artists, and gamelan enthusiasts still exists in the community. The program's goal is to initiate gamelan festivals on campus and in the community. The methods used include holding festivals with multi-collaborations, ensuring campus support, collaborating with artists, holding regular festivals, building interaction with gamelan groups, evaluating and improving program quality, and collaborating with relevant institutions. The program's results include the implementation of gamelan festivals at UGM from 2017 to the present, increased public interest in participating in gamelan festivals, increased community enthusiasm for gamelan practice, more functional gamelan instruments in the community, university institutions playing an increasing role in cultural preservation, and support for government institutions in programs to advance traditional culture. The conclusion of the implementation of the gamelan festival program is that there are increasingly more activities to preserve the art of gamelan on campus and in the community, gamelan instruments in the community are becoming more functional, and the enthusiasm of institutions in advancing traditional culture is increasing.Seni tradisional cenderung kalah pamor dibanding budaya pop. Hal ini juga terjadi pada seni karawitan Jawa. Perangkat gamelan banyak yang mangkrak dan keinginan masyarakat untuk terlibat dalam melestarikan karawitan menurun. Salah satu sebabnya adalah minimnya ruang pementasan padahal potensi perangkat gamelan, seniman pendukung, dan peminat karawitan masih ada di masyarakat. Tujuan program adalah menginisiasi kegiatan festival karawitan di kampus dan masyarakat. Metode yang dilakukan: memastikan dukungan kampus, bekerja sama dengan seniman, menggelar festival secara rutin, membangun interaksi dengan kelompok-kelompok karawitan, mengevaluasi dan meningkatkan kualitas program, dan kerjasama dengan lembaga terkait. Hasil program yang telah dilakukan: terselenggaranya kegiatan festival karawitan di UGM dari tahun 2017 hingga kini, semakin meningkatnya animo masyarakat untuk mengikuti kegiatan festival karawitan, meningkatnya semangat masyarakat dalam berlatih karawitan, perangkat gamelan di masyarakat lebih berfungsi, institusi universitas semakin berperan dalam pelestarian budaya, dan mendukung semangat lembaga pemerintah dalam program pemajuan kebudayaan tradisional. Kesimpulan hasil penyelenggaraan program festival karawitan  adalah semakin maraknya kegiatan melestarikan seni karawitan di kampus dan masyarakat,  perangkat gamelan di masyarakat semakin berfungsi, dan meningkatnya semangat institusi dalam memajukan kebudayaan tradisional.